Experimental cultivation of Spirulina platensis using My An mineral water, Thua Thien Hue province - Nguyet, Vu Thi; Kim, Dang Dinh; Chuyen, Nguyen Hong; Tam, Vu Thi Thanh; Ha, Tran Phuong; Cuong, Pham Viet; Huu Dat, Ton That; Bich Ngoc, Hoang Phan; Thu Thuy, Nguyen Thi (Vietnam Journal of Science and Technology, 2017)
Spirulina platensis was experimentally cultivated by semi-continuous method at 20m2 scale pilot to effectively use the available bicarbonate and minerals of the My An mineral water, Phu Vang district, Thua Thien Hue province, and reduce production cost. Analyses of My An water quality showed that this mineral water source was suitable to cultivate Spirulina Platensis after removing H2S. The average algal yield reached to 10gDW/m2.day. The obtained algal biomass contained high nutrient compositions and was a suitable source for functional food (68.32 % protein, 7.32 % lipids containing Omega-3 and Omega-6, and low heavy metal concentration). The obtained results indicated that the My An mineral water source was indeed a suitable water source for producing Spirulina platensis biomass as a functional food.